Experimentally induced diabetes causes glial activation, glutamate toxicity and cellular damage leading to changes in motor function - Nagayach, Aarti; Patro, Nisha; Patro, Ishan (Frontiers in Cellular Neuroscience, 2014)
Behavioural impairments are the most empirical consequence of diabetes mellitus documented in both humans and animal models, but the underlying causes are still poorly understood. As the cerebellum plays a major role in coordination and execution of the motor functions, we investigated the possible involvement of glial activation, cellular degeneration and glutamate transportation in the cerebellum of rats, rendered diabetic by a single injection of streptozotocin (STZ; 45mg/ kg body weight; intraperitoneally). Motor function alterations were studied using Rotarod test (motor coordination) and grip strength (muscle activity) at 2nd, 4th, 6th, 8th, 10th and 12th week post diabetic confirmation. Scenario of glial (astroglia and microglia) activation, cell death and glutamate transportation was gauged using immunohistochemistry, histological study and image analysis. Cellular degeneration was clearly demarcated in the diabetic cerebellum. Glial cells were showing sequential and marked activation following diabetes in terms of both morphology and cell number. Bergmann glial cells were hypertrophied and distorted. Active caspase-3 positive apoptotic cells were profoundly present in all three cerebellar layers. Reduced co-labelling of GLT-1 and GFAP revealed the altered glutamate transportation in cerebellum following diabetes. These results, exclusively derived from histology, immunohistochemistry and cellular quantification, provide first insight over the associative reciprocity between the glial activation, cellular degeneration and reduced glutamate transportation, which presumably lead to the behavioural alterations following STZ-induced diabetes.